A Teaching Proposal to Develop English Students' Speaking Skills from Tenth and Eleventh Grades in Public High Schools - Moreira González, Yamileth (2014)
The main objective of this article is to provide teachers who teach English as a foreign language in public academic schools with a teaching approach to strengthen the oral production of English in tenth and eleventh graders by using the content of the syllabus of the Education Ministry (MEP). One specific objective of this is to encourage the use of participatory and transactional oral strategies to address daily life situations to interact and get a mutual understanding. The other one is to increase vocabulary and technical, formal and informal language to be used in workplaces and everyday situations.  Linguistic structures are presented in every level and content included in the tenth and eleventh levels as well as sample situations that will lead English teacher  to develop other situations based on the needs of the group and the creativity of the students.